A Web-Based Operating Room Management Educational Tool. Issue 3 (1st August 2016) - Tsai, Mitchell H.; Haddad, Daniel J.; Friend, Alexander F.; Bender, S. Patrick; Davidson, Melissa L.
Abstract : In 2010, our department instituted a nonclinical, administrative rotation in operating room management for anesthesiology residents. Subsequently, we mandated the rotation for all senior anesthesiology residents in 2013. In 2014, under the auspices of the American Society of Anesthesiologists, we developed a web-based module covering the basics of finance, accounting, and operating room management. A multiple-choice test was given to residents at the beginning and end of the rotation, and we compared the mean scores between residents who took the traditional course and residents who took the web-based module. We found no significant difference between the groups of residents, suggesting that the web-based module is as effective as traditional didactics.